2024
DOI: 10.3389/fimmu.2024.1302761
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint ligands expressed on mature high endothelial venules predict poor prognosis of NSCLC: have a relationship with CD8+ T lymphocytes infiltration

Jing Luo,
Xiuhuan Shi,
Yumeng Liu
et al.

Abstract: BackgroundAn insufficient number of intratumoral CD8+ T lymphocytes is a major barrier to antitumor immunity and immunotherapy. High endothelial venules (HEVs) are the major sites through which lymphocytes enter tumors; however, the molecular mechanism through which HEVs mediate CD8+ T lymphocyte infiltration remains poorly understood.MethodsForty-two patients with stage IIIA lung adenocarcinoma, who underwent surgery, were recruited. Multiplex immunohistochemical staining was conducted on tumor tissues to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…demonstrated that the rapid generation of synthetic human HEV-like structures by a tissue-bioengineering approach effectively enabled the formation of lymphoid structures with TLS functional properties in vivo , which acted as lymphatic hubs facilitating T cell infiltration into the TME and eliminate tumor cells ( 31 ). Mature HEVs, rather than lymphatics or blood vessels, have been shown to mediate CD8 + T cell infiltration, whereas the immune checkpoint ligands expressed on mature HEVs could negatively regulate CD8 + T cell entry into TLSs ( 32 ). There is currently still a debate to which extent TA-HEVs are necessary to actively influence cancer progression in TLSs or TLS-like structures ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that the rapid generation of synthetic human HEV-like structures by a tissue-bioengineering approach effectively enabled the formation of lymphoid structures with TLS functional properties in vivo , which acted as lymphatic hubs facilitating T cell infiltration into the TME and eliminate tumor cells ( 31 ). Mature HEVs, rather than lymphatics or blood vessels, have been shown to mediate CD8 + T cell infiltration, whereas the immune checkpoint ligands expressed on mature HEVs could negatively regulate CD8 + T cell entry into TLSs ( 32 ). There is currently still a debate to which extent TA-HEVs are necessary to actively influence cancer progression in TLSs or TLS-like structures ( 17 ).…”
Section: Discussionmentioning
confidence: 99%